Atherogenesis and metabolic dysregulation in LDL receptor–knockout rats - Srinivas D. Sithu; Marina V. Malovichko; Krista A. Riggs; Nalinie S. Wickramasinghe; Millicent G. Winner; Abhinav Agarwal; Rihab E. Hamed-Berair; Anuradha Kalani; Daniel W. Riggs; Aruni Bhatnagar; Sanjay Srivastava (JCI Insight, 2017)
Mechanisms of atherogenesis have been studied extensively in genetically engineered mice with disturbed cholesterol metabolism such as those lacking either the LDL receptor (Ldlr) or apolipoprotein E (apoe). Few other animal models of atherosclerosis are available. WT rabbits or rats, even on high-fat or high-cholesterol diets, develop sparse atherosclerotic lesions. We examined the effects of Ldlr deletion on lipoprotein metabolism and atherosclerotic lesion formation in Sprague-Dawley rats. Deletion of Ldlr resulted in the loss of the LDLR protein and caused a significant increase in plasma total cholesterol and triglycerides. On normal chow, Ldlr-KO rats gained more weight and were more glucose intolerant than WT rats. Plasma proprotein convertase subtilisin kexin 9 (PCSK9) and leptin levels were higher and adiponectin levels were lower in KO than WT rats. On the Western diet, the KO rats displayed exaggerated obesity and age-dependent increases in glucose intolerance. No appreciable aortic lesions were observed in KO rats fed normal chow for 64 weeks or Western diet for 16 weeks; however, after 34–52 weeks of Western diet, the KO rats developed exuberant atherosclerotic lesions in the aortic arch and throughout the abdominal aorta. The Ldlr-KO rat may be a useful model for studying obesity, insulin resistance, and early-stage atherosclerosis.